Postantibiotic Effects of Gatifloxacin against Gram-Positive and -Negative Organisms - Pankuch, G. A. (American Society for Microbiology, 1999)
Gatifloxacin pneumococcal, staphylococcal and enterococcal postantibiotic effects (PAEs) were 0.5 to 4.0 h, respectively. For Escherichia coli and Pseudomonas aeruginosa, PAEs were 2.2 to 4.8 h. Pneumococcal, staphylococcal, and enterococcal postantibiotic sub-MIC effects (PA-SMEs) (four times the MICs) were 3.7 to 8.6, 2.3 to 3.8, and 1.6 h, respectively, and E. coli and P. aeruginosa PA-SMEs were ≥9.6 and 4.4 h, respectively.